Design of broadband metamaterial near-perfect absorbers in visible region based on stacked metal-dielectric gratings. (13th June 2018) - Mao, Qianjun; Feng, Chunzao; Yang, Yizhi; Tan, Yingjie
Abstract: A broadband near-perfect absorber in the visible region has been designed in this paper. This absorber consists of an alternating stack of metallic gratings and dielectric layers on the basis of a metallic substrate. Absorptivity and electromagnetic field distributions of the structure via the finite difference time domain (FDTD) method have been stimulated. The results show that the average absorptance of the absorber exceeds 95.2% in the wavelength range from 350 nm to 650 nm. The enhanced absorption can be ascribed to several mechanisms including surface plasmon polaritons, magnetic polaritons, and Fabry–Perot resonances. Besides, geometric effects on the resonance wavelengths have been investigated. Moreover, the effects of oblique incidence and polarization states on the spectral absorption have been analyzed. This designed absorber will be worth applying in solar energy harvesting via combining the study results mentioned above.